1986
DOI: 10.1073/pnas.83.19.7472
|View full text |Cite
|
Sign up to set email alerts
|

Glucocerebrosidase processing in normal fibroblasts and in fibroblasts from patients with type I, type II, and type III Gaucher disease.

Abstract: Fibroblasts from normal subjects and pa- patients with the different types of Gaucher disease using rabbit antisera and suggested that type I disease might be due to a processing error. In our own studies, using affinity-purified heterosera and monoclonal antibodies, we found only a 63-kDa antigen in normal fibroblasts and fibroblasts from patients with type I and type III Gaucher disease. No band was visualized in type II disease. We suggested that the other bands that had been observed by Ginns et al. repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Early pulse-chase studies of patient fibroblasts [43,44] indicated that the L444P mutation leads to an unstable protein with incompletely processed carbohydrate chains. This observation was later confirmed by recombinant expression in 3T3 and Sf9 cells [35,42,45].…”
Section: L444p and G202r Mutationsmentioning
confidence: 99%
“…Early pulse-chase studies of patient fibroblasts [43,44] indicated that the L444P mutation leads to an unstable protein with incompletely processed carbohydrate chains. This observation was later confirmed by recombinant expression in 3T3 and Sf9 cells [35,42,45].…”
Section: L444p and G202r Mutationsmentioning
confidence: 99%
“…Since only single forms (63 kilodaltons) of normal human acid ß-glu cosidase were expressed in COS-1 or Sf9 cells, alternative expression systems will be required to evaluate putative étiologie single base substitutions for these variants. In con trast, several variants of type 1 Gaucher dis ease have been shown to have abnormal active site function [3,11,13,15,26,29] and unaltered glycosidic processing [3,6,8,33, Bergman and Grabowski, unpublished ob servation]. Expression of DNAs from this group of Gaucher variants in Sf9 cells and evaluation of the expressed acid ß-glucosi dase with probes of active site function should allow for the distinction between artifactual or polymorphic and étiologie base substitutions.…”
Section: Discussionmentioning
confidence: 99%
“…In cul tured fibroblasts, several variants of types 1, 2 and 3 Gaucher disease have been found to have residual mutant enzymes with appar ently intact active site function [6,26,27], but altered post-translational oligosaccha ride remodelling [6, Bergman and Grabowski, unpublished observation] and intracellu lar stabilities [6,8]. On immunoblotting or by pulse-chase processing studies the causal mutations in these variants give leads to sin gle forms of acid ß-glucosidase (usually 63-64 kilodaltons).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-GCR antibodies are important and useful tools to characterize GCR produced in a number of expression systems, including insect cells [9,20], plant cells [18] and mammalian cells [21][22][23]. Anti-GCR antibodies can also be used to discriminate between non-neuropathic and neuropathic cases of this disorder, as demonstrated by Ginns and collaborators [24,25], and to characterize the molecular forms of the enzyme in normal individuals and in patients with Types I, II and III forms of the disease [3,11,[26][27][28][29]. So far, anti-GCR antibodies (both monoclonal and polyclonal) have been produced against purified GCR from human placenta [24,30,31].…”
Section: Introductionmentioning
confidence: 99%